Pengembangan Agribisnis Pedesaan Melalui Pemanfaatan Kulit Kakao Sebagai Sumber Pektin - Elvira Iskandar; Cut Erika (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACT. The development of food industry in Indonesia has increased the demand and domestic consumption of pectin. Cocoa skin is potentially used to produce pectin as the raw material of industry. This study aimed to determine the effect of treatments on raw material, the medium and pH extraction to the characteristics of the pectin produced from cocoa skin, and to analyse the economic feasibility of pectin production from cocoa skin. Production was started with pectin extraction using citric acid solvent to some variables : 1) type of raw material (fresh and dried), 2) extraction time (60 and 90 minutes), and 3) pH of the extraction (2.5 and 3.5), then was continued by clotting with 95% ethanol, washing and drying of pectin. Economic analysis was done through analysis of break-even point (BEP) and the return cost ratio (RCR) to determine the level of benefits and feasibility of cocoa skin utilization. The results showed that the research treatments produced 5.6% - 6.7% pectin from initial weight of cocoa skin used, and the moisture content was 8.7% - 9.58%. Total revenue of the business is IDR 1.340.000/ month with a total production cost of IDR 1.000.300/ month. RCR value of 1.34 and BEP quantity of 2 kg showed that cocoa skin processing industry profitable to be implemented.